Physics and chemistry of producing silicon-hydroxylapatite-titanium composite materials; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Golovanova O. A.; Zayts A. V.; Panova T. V.; Frangulyan (Franguljyan) Т. S. Tamara Semenovna (2015, 2015)
Title screen